William James’ pluralistic panapsychism - Piróg, Mirosław (Folia Philosophica, 2007)
The aim of this article is to present one of the most important motives of William James’ late philosophy referred to as pluralisic panpsychism. James considered the alternative, such as monism-pluralism, as the most important philosophical theme. In the article, his version of pluralism in relation to the categories of novelty and indeterminism is presented. Next, it is shown that James’ panpsychism can be interpreted as the result of the presence of non-dualistic tendencies in his philosophy. In conclusion, it is indicated that the category of panpsychism has not been developed.